Predictors of hospital prenotification for STEMI and association of prenotification with outcomes. Issue 9 (14th December 2021) - Blusztein, David; Dinh, Diem; Stub, Dion; Dawson, Luke; Brennan, Angela; Reid, Christopher; Smith, Karen; Nehme, Ziad; Andrew, Emily; Bernard, Stephen; Lefkovits, Jeffrey
Abstract : Background: Delay to reperfusion in ST-elevation myocardial infarction (STEMI) is detrimental, but can be minimised with prehospital notification by ambulance to the treating hospital. We aimed to assess whether prenotification was associated with improved first medical contact to balloon times (FMC-BT) and whether this resulted in better clinical outcomes. We also aimed to identify factors associated with use of prenotification. Methods: This was a retrospective study of prospective Victorian Cardiac Outcomes Registry data for patients undergoing primary percutaneous coronary intervention for STEMI from 2013-2018. Postcardiac arrest were excluded. Patients were grouped by whether they arrived by ambulance with prenotification (group 1), arrived by ambulance without prenotification (group 2) or self-presented (group 3). We compared groups by FMC-BT, incidence of major adverse cardiac and cerebrovascular events (MACCE), mortality and factors associated with the use of prenotification. Results: 2891 patients were in group 1 (79.3% male), 1620 in group 2 (75.7% male) and 1220 in group 3 (82.9% male). Patients who had prenotification were more likely to present in-hours (p=0.004) and self-presenters had lowest rates of cardiogenic shock (p<0.001). Prenotification had shorter FMC-BT than without prenotification (104 min vs 132 min, p<0.001) Self-presenters had superior clinical outcomes, with no difference between ambulance groups. Groups 1 and 2 had similar 30-day MACCE outcomes (7.4% group 1 vs 9.1% group 2, p=0.05) and similar mortality (4.6% group 1 vs 5.9% group 2, p=0.07). In multivariable analysis, male gender, right coronary artery culprit and in-hours presentation independently predicted use of prenotification (all p<0.05). Conclusion: Differences in clinical characteristics, particularly gender, time of presentation and culprit vessel may influence ambulance prenotification. Ambulance cohorts have high-risk features and worse outcomes compared with self-presenters. Improving system inequality in prehospital STEMI diagnosis is recommended for fastest STEMI treatment.